Design and fabrication of an all-composite stabilizer section - Lim, Chien Kai. (2011)
In this project, design, development and manufacturing by co-curing of a 3D aerofoil structure was demonstrated by fabricating a typical tapered tail section with two C-spars running through its entire span. The C-spar is bonded at its flange with the skin of the tail section and this forms the main structural member of the section that carries the flight loads and weight of the tail. A study of co-curing techniques was first conducted and several designs were compared and evaluated. The 3 piece hollow mold design for repeatable autoclave curing was developed and proved to be advantageous over other methods. An initial sample fabrication carried out was studied to optimize the tail fabrication process before the full scale mold parts were machined. The set of mold parts with design features to achieve good tolerance and ease of flexibility in repair and reconstruction was produced. An evaluation of the manufacturing process revealed the C-spar flange spring back during lay-up as the main challenge that affects the quality of the co-cured tail section.